(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The given article is aimed to reveal the benefits of using AI in the process of teaching English to young learners. According to future prospects day by day the role of artificial intelligence can rise in each sphere of humanity. Especially, the usage of AI in teaching English is increasing day by day as it is the demand of XXI century. The utilization of Artificial intelligence in the process of teaching foreign language makes the lesson more productive and enthusiastic.